Towards the development of a thulium-doped all-fibre laser - Kgomo, Mosima B (My University, 2018)
Fibre based lasers have become a dominant laser architecture due to high output powers and efficiencies, compact form factors, and excellent beam quality. Double-clad large mode area fibres (DC-LMAF) are required to achieve high output power (up to kW level). The performance and integrity of the thulium-doped all-fibre laser is critically dependent on the quality of splices between different components constituting the fibre laser. Power loss at the splice joints (splice loss) has a deleterious effect on the performance and long-term reliability of high power fibre lasers. Splice losses, caused by poor fusion splices, lead to a decrease in the optical-to-optical efficiency as well as degradation in the beam quality of fibre lasers. The low-loss, wavelength-dependent fusion splices are required for the development of the high power thulium-doped all-fibre laser that is known to lase in the 2000 nm wavelength region. A spectral splice loss measurement technique was constructed to measure splice loss between two 25/400 µm passive DC-LMAF in the 2000 nm spectral region. The different types of aspects that can lead to splice loss measurement variations are investigated and mitigated. The 0.03% was the expected splice loss measurement variation. The optimal parameter set points for fusion splicing two 25/400 µm passive DC-LMAF were found through conducting a splice loss optimization experiment. The fractional factorial design of experiment which enables the reduction of the required number of experiments by performing them at a certain specific combination of parameters was applied due to the seven large number of splice parameters that required to be optimized. A total of 18 experiments were conducted based on the fractional factorial design of experiment that followed the Taguchi orthogonal methodology. The splice loss results were analysed by using a statistical technique, the analysis of variance (ANOVA). The Gap Distance and Arc Time 2 splice parameters were revealed to be the two most important parameters that have an impact on fusion splice quality by contributing 32% and 27% towards splice loss, respectively within the chosen splice parameter levels for this work.
A thesis submitted in fulfillment of the requirements for the degree of Masters in Science, in the School of Physics, University of the Witwatersrand, Johannesburg, 2018
Keywords: Thulium; Fiber optics